The Shape of the Kingdom of God in the Psalter - Ellison, Davy (2025)
The king and the kingdom of God are implicit and pervasive subjects throughout Scripture and many studies of these themes rightly focus on the king. There is, however, more to be considered. This article seeks to examine the shape of the kingdom of God in the Psalter and does so by focussing primarily on place (Zion) and people (victory over enemies), although a consideration of power (the king) is not absent. The article concludes that the dominant profile of the kingdom in the Psalter not only aligns with its description elsewhere in Scripture but also forms a matrix from which the fuller New Testament expressions emerge. The Psalter therefore provides a key Old Testament context for understanding the kingdom of God in its canonical fulness, and how it is recognised as good news.
Keywords: Kingdom of God; Zion; Biblical Theology; Enemies; King; Psalter